HUBUNGAN ANTARA INTRA-ABDOMINAL PRESSURE (IAP) DENGAN TEKANAN VENA JUGULARIS PASIEN DI IRD RSU BANGLI - Kamayani, Made Oka Ari; Suardana, I Wayan (Coping: Community of Publishing in Nursing; Vol 4 No 3 (2016): Desember 2016, 2016)
Increased of Intra-Abdominal Pressure (IAP) affects the blood flow on various organs, such as the cardiovascular, respiratory, renal and nervous system. This condition also play an important role in the prognosis of patients. Increased of IAP pressing the diaphragm thus decreasing the size of the thoracic cavity and causes increased the pressure of  intrathoracial. This  high pressure will increase the jugular venous pressure and impede the venous return from the brain. This can cause the  increased of  intracranial pressure and impact on the blood flow to the cerebral. The purpose of this study was to determine the correlation between the IAP with jugular venous pressure. This research uses a correlational descriptive design with cross sectional design and  implemented in Emergency Department of Bangli Hospital. The results of this research show the average value of the IAP is 9.82 cmH2O and the average value of the jugular venous pressure is 7.23 cm. The Spearman Rank test with ? = 0.05, p value = 0.238, which means there is no correlation between the IAP and jugular venous pressure. Keywords : Intra-Abdominal Pressure, jugularis venous pressure